The Association between Mycoplasma pneumoniae Genotype and Cutaneous Disease - Jasna Rodman Berlot; Tatjana Mrvič; Mitja Košnik; Darja Keše (Microorganisms, 2023)
Mycoplasma pneumoniae (Mp) can cause several extrapulmonary manifestations, most frequently dermatological ones. It is largely unknown whether Mp genotype determines Mp-induced cutaneous disease. The aim of our study was to assess the association between Mp genotype and this clinical outcome. We performed a retrospective study of children referred with signs of acute Mp infection from 1 January 2014 to 31 December 2014. We compared the characteristics of children presenting as cutaneous disease, upper (URTI) and lower respiratory tract infection (LRTI). In addition, we separately analyzed the data of patients presenting with Mp-induced cutaneous disease. We evaluated data from 435 patients (mean age 7.3 years, SD 3.4 years; 52.0% boys) who had Mp PCR-positive pharyngeal swab, P1 genotype and/or multilocus variable-number tandem-repeat analysis (MLVA) genotype defined and no viral co-detection, presenting as cutaneous disease (38/435), URTI (46/435) or LRTI (351/435). The majority of patients had urticarial (55%, 21/38) or maculopapular eruptions (37%, 14/38). We found no association between Mp genotype and clinical outcome of cutaneous disease, nor any specific dermatological presentation. In the group with cutaneous disease, 18% (7/38) required hospital admission because of rash. We found that infection with MLVA-3,6,6,2 strains was more common in admitted patients than in outpatients (40% vs. 4%, p = 0.017) and significantly affected the likelihood of hospital admission in a logistic regression model. The results of our cohort study suggest that Mp genotype does not determine Mp-induced cutaneous disease or a specific dermatological presentation. Nevertheless, infections with certain MLVA strains could induce more severe cutaneous disease requiring hospitalization.